Інноваційна діяльність в Україні: сучасний стан та перспективи розвитку - Максименко, Яна Анатоліївна (Харківський національний аграрний університет ім. В. В. Докучаєва, 2018)
У статті досліджено проблеми інноваційного розвитку національної економіки. Охарактеризовано сучасний стан інноваційної діяльності в Україні та виявлено проблеми в даній сфері. Показано місце України в рейтингу країн світу за глобальним інноваційним індексом. Проаналізовано ряд показників, що впливають на інноваційну діяльність. Розроблено рекомендації, спрямовані на розвиток інноваційної діяльності в Україні.

The article deals with the issues of innovation development of national economy. The subject of research is abstract theorem and practical guidelines of the analysis and perspectives of development of innovation activity. The aim of the article is the analysis of the contemporary state of innovation activity in Ukraine, revealing problems in the field and besides elaborating recommendations aimed at the development of innovation activity. Methods of research. The article uses the following methods: systemic approach, generalization, analysis and synthesis, statistical methods, graphical methods. The results of research. The article characterizes the contemporary state of innovation activity in Ukraine. The paper analyzes the place of Ukraine in terms of the global innovation index. The article reveals problems in this sphere: the technologically low level of national economy, the underfinancing of scientific research inventions, especially by the state budget and foreign investment, financing instability. The article analyses a number of factors that influence innovation activity, among which there are expenditures connected with scientific research and development in GDP, dynamics and structure of financing of innovation activity, the structure of doing scientific research in various sectors of activity. The article states that expenditures connected with scientific research and development in GDP is growing annually in EC countries over the past years, whereas Ukraine demonstrates a negative dynamics of this factor. When analyzing the dynamics and structure of financing of innovation activity in Ukraine, the article reveals that the total sum of innovation expenditures fluctuates cyclically, among the sources of funding of innovation activity proprietory funds dominate considerably, state budget funds and investment having a minor part in the expenditures on innovations. The biggest proportion of the researchers are from the state sector, a minor part are from business sector and higher education. The article elaborates recommendations aimed at development of innovation activity, first of all this is growth and stability of financing of innovation activity, development of a system of steps that will promote attracting of financial resources of foreign investors and also encouraging businessmen doing scientific research. These measures will unlock a high scientific potential. The sphere of the results implementation. The results of the research can be put into practice to develop innovation activity.
Innovation activity in Ukraine: the contemporary state and development perspectives
Keywords: інновації; розвиток інноваційний; дослідження наукові; фінансування; innovations; innovation development; scientific research; financing